El impacto del tratado de libre comercio Perú-Estados Unidos en la exportación del espárrago fresco peruano a Estados Unidos: un estudio para los años 2004-2018 - Vivar Coronado, Andrea Sofía (2021)
Peru is considered as the main exporter of fresh asparagus in the world. Also, its main trading partner is the United States which imports more than 40% of the asparagus produced in the world. The present investigation is based on the fact that Peru and the United States keep the Free Trade Agreement (FTA) in force since 2009, which provides the Peruvian country with benefits derived from the elimination of tariff barriers. However, some experiences form neighboring countries, like as Chile, Colombia and Ecuador, show that, not always a country improves or benefits from a trade agreement and that each case must be studied in a particular way since even at the sectoral level there are differences in the wellness. That is why the question which focuses on analyzing the impact of the entry into force of the aforementioned treaty and on verifying whether the application of it meant a considerable increase in Peruvian fresh asparagus exports to the United States. Likewise, it is relevant to study and measure other variables that may be cause of the phenomenon, such as international prices, terms of trade, and the real exchange rate, which will serve as tools when calculating the impact of NAFTA. To do this, an econometric methodology was used in which, by means of an ordinary least squares estimation, it was possible to reach the conclusion that there is evidence of the positive impact of Free Trade Agreement. Time series data was used on a monthly basis from 2004 to 2018 and a dummy variable was included. Finally, after correcting the unit root and autocorrelation problem, it was possible to reach the conclusion that, in the presence of the trade agreement, the monthly variation of the export of fresh Peruvian asparagus to the United States is increased by 0.23% or 15,705 dollars (in FOB value). This figure reflects that, although the FTA has a positive effect on asparagus exports, the presence of unfavorable conditions in said agreement prevents a better result.